Traditional Rituals of the Kampung Kuta Community for Mothers and Babies After Childbirth - Syahriadi, M. Azril Fathulloh; Sondarika, Wulan; Herawati, Titi Dwi; Nanda, Adjeng Dheannisya Euis; Nurafni, Yasmin; Sulistiawati, Adella (Universitas Galuh, 2025)
In the treatment of mothers and babies after childbirth, the community of kampung Kuta still has high beliefs and traditional rituals that have been passed down from generation to generation from the ancestors. This study aims to explore more deeply how the practice of postnatal maternal and infant care is based on the perspective of local culture in the traditional village of Kuta, Ciamis district. Data were collected in 2025 through in-depth interviews with aki Warja who is one of the traditional leaders or elders in the village of Kampung, Ciamis district. Thematic analysis was conducted using thematic analysis, where key themes relating to postnatal mother and baby care, family support, and integration of modern health services were identified. The treatment rituals of pregnant women in the community are part of the culture and customs of the local community, although they may differ from modern medical views, these rituals have an important meaning in maintaining the health and safety of pregnant woman and their babies. There are a number of taboos that must be obeyed by pregnant women, traditional knowledge and modern medical knowledge can provide optimal results in efforts to improve the quality of pregnancy in the local village.